Phloridzin Highly Accumulated in Malus rockii Rehder and Its Structure Revision and Hypolipidemic Activity - Lang, Li-Juan; Wang, Min; Lei, Chang; Shen, Yi; Zhu, Qi-Jie; Diao, Hong-Mei; Chen, Hao; Shen, Lei; Dong, Xiang; Jiang, Bei; Xiao, Chao-Jiang (Planta Medica, 2022)
Phloridzin is a lead compound of the prestigious antidiabetic gliflozins. The present study found that phloridzin highly accumulated in Malus rockii Rehder. The content of phloridzin in M. rockii was the highest among wild plants, with the percentage of 15.54% in the dry leaves. The structure of phloridzin was revised by proton exchange experiments and extensive 2D NMR spectra. Phloridzin exhibited significant hypolipidemic activity in golden Syrian hamsters maybe by increasing the expression of CYP7A1, at the doses of 50 mg/kg and 200 mg/kg. The total performance of anti-hyperlipidemic effect of phloridzin may be superior to that of lovastatin, though lovastatin was more active than phloridzin. In addition, phloridzin exhibited moderate antimalarial activity with inhibition ratio of 31.3 ± 10.9% at a dose of 25 mg/kg/day, and showed moderate analgesic activity with 28.0% inhibition at a dose of 50 mg/kg.
Keywords: Malus rockii; Rosaceae; phloridzin; hypolipidemic activity; antimalarial activity; analgesic activity